Catalogue of Herpetological types in the collection of the Raffles Museum of Biodiversity Research, National University of Singapore - Das, Indraneil; K., Kelvin P. Lim (National University of Singapore, 2001)
The Raffles Museum ofBiodiversity Research, which incorporates the Zoological Reference Collection at the National University of Singapore, contains the largest zoological reference collection in south-east Asia. Being the inheritor of the collections of the old Raffles Museum, and subsequently, the National Museum, it is a respository of historical specimens collected by pioneering south-east Asian biologists including R. Hanitsch, J. C. Moulton, F. N. Chasen and M. W. F. Tweedie. Name-bearing types of some of the older specimens appeared in papers authored by M. A. Smith and W. Hennig, among others. In the catalogue of herpetological types compiled here, types ofseven amphibian and 13 reptile species are indicated, comprising a total of 48 type material (nine holotypes, 27 paratypes and 12 syntypes).